2012
DOI: 10.1093/acprof:oso/9780195176667.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Parricide

Abstract: This book is about juvenile and adult sons and daughters who kill their parents. The book moves far behind the statistical correlates of parricide by synthesizing the professional literature on parricide in general, matricide, patricide, double parricides, and familicides. The book explains the reasons behind the killings and includes in-depth discussion of issues related to prosecuting and defending parricide offenders. The book is enriched with its focus on clinical assessment, case studies, and follow-up of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 202 publications
0
2
0
Order By: Relevance
“…These studies reported either that the majority of examined juvenile parricide offenders completed a successful transition to society after the homicide or that this group of offenders spent less time in prison than other types of JHOs. Other research on juveniles who killed or attempted to kill their parents presented more mixed results, and highlighted cases of parricide offenders who continued to engage in criminal behavior after their release from custody [20][21][22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…These studies reported either that the majority of examined juvenile parricide offenders completed a successful transition to society after the homicide or that this group of offenders spent less time in prison than other types of JHOs. Other research on juveniles who killed or attempted to kill their parents presented more mixed results, and highlighted cases of parricide offenders who continued to engage in criminal behavior after their release from custody [20][21][22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Current literature on these rare phenomena is mainly limited to case studies and descriptive statistics to explain offender, victim, and event characteristics. Findings show that most parricides and siblicides are committed by male offenders (Heide, 2013;Heide & Frei, 2010;Liem & Reichelmann, 2014;Marleau et al, 2006;Peck & Heide, 2012). In a recent study analyzing multiple family homicides, Liem and Reichelmann (2014) identified an extended parricide typology that involved cases of offenders killing their parents and siblings.…”
Section: Family Mass Murdermentioning
confidence: 99%